Lanthanide triangles sandwiched by tetranuclear copper complexes afford a family of hendecanuclear heterometallic complexes [Ln(III)3Cu(II)8] (Ln = La-Lu): synthesis and magnetostructural studies - Iasco, Olga; Novitchi, Ghenadie; Jeanneau, Erwann; Luneau, Dominique (Inorganic chemistry, 2013)
Reaction in ethanol of 3-hydroxymethylen-5-methylsalicylaldoxime (H3L) with CuCl2·2H2O and LnCl3·xH2O [Ln = La (1), Ce (2), Pr (3), Nd (4), Eu (5), Gd (6), Tb (7), Dy (8), Er (9), Yb (10), Lu (11), Ho (12)] allowed the synthesis of a family of hendecanuclear heterometallic copper(II)-lanthanide(III) clusters with general formula [Ln(III)3Cu(II)8(HL)6(μ4-O)2Cl6(H2O)8]Cl3 (1-12). According to the single-crystal X-ray diffraction investigation, the complexes are isomorphous and crystallize in the trigonal R32 group. The hendecanuclear cluster is formed by two tetrahedral μ4-oxo Cu4 clusters assembled by three lanthanide ions sandwiched in between. Along the family, the separation between the Cu4 moieties increases linearly from Lu to La in good correlation with ionic radius of the lanthanide ions. A comparative analysis of the magnetic data for the lanthanum (1) and lutetium (11) compounds shows the presence of ferromagnetic and antiferromagnetic interactions within the μ4-oxo Cu4 moieties. For the gadolinium (6) and terbium (7) compounds, the magnetic interactions between the lanthanide and the copper ions are found to be ferromagnetic. The dysprosium (8) compound exhibits single-molecule magnet behavior.